New energy automobile power battery cooling liquid and preparation method thereof

By using specific nanoadditives and antifoaming agents in the coolant of power batteries of new energy vehicles, an efficient thermal conductivity network is formed, and the problem of insufficient anti-freezing performance and stability is solved, and low dielectric constant, high thermal conductivity and good storage stability are achieved.

CN120399649AActive Publication Date: 2025-08-01AMER TECH CO LTD

Patent Information

Application Number
CN202510434797.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-08
Publication Date
2025-08-01
Estimated Expiration
2045-04-08

AI Technical Summary

Technical Problem

The existing new energy vehicle power battery coolant has shortcomings in its anti-freezing performance and stability, and the stability of nanomaterials has not received attention.

Method used

Specific nanoadditives and antifoaming agents, including ionic sheet nanominerals such as montmorillonite nanosheets and hydrotalcite nanosheets, as well as nanodiamonds, are used to form an efficient thermal conductivity network, enhance storage stability, and improve stability through preferred antifoaming agents.

Benefits of technology

It achieves low dielectric constant, high thermal conductivity and good storage stability, improves thermal conductivity and reduces electrical conductivity, and expands the temperature range of use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005349244810000081
    Figure BDA0005349244810000081
  • Figure BDA0005349244810000091
    Figure BDA0005349244810000091
Patent Text Reader

Abstract

The invention belongs to the technical field of battery cooling liquid, and particularly relates to new energy automobile power battery cooling liquid and a preparation method thereof. The new energy automobile power battery cooling liquid is prepared from the following raw materials in percentage by mass: 40 to 60 percent of dihydric alcohol, 0.2 to 3 percent of a corrosion inhibitor, 0.1 to 0.5 percent of an antioxidant, 0.1 to 0.5 percent of a pH regulator, 0.01 to 0.05 percent of an anti-foaming agent, 0.005 to 0.015 percent of a nano additive and the balance of ionized water, the nano additive comprises an ionic flaky nano mineral, nano palygorskite and nano diamond in a mass ratio of (3-5): (0.1-0.5): (0.1-0.5). The new energy automobile power battery cooling liquid has good low dielectric constant, high thermal conductivity and good storage stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery coolants, and particularly relates to a power battery coolant for new energy vehicles and a preparation method thereof. Background Art

[0002] In recent years, new energy vehicles have developed rapidly. The key components of new energy vehicles include power batteries, motors, and electric systems. Due to high-power charging and discharging, power batteries generate a large amount of heat during use, and their thermal management systems directly affect the performance, safety, and service life of power batteries. Common cooling methods for power batteries include air cooling, phase change cooling, and liquid cooling. Air cooling has insufficient heat dissipation capacity, and phase change liquid cooling is not easy to be lightweight, so their applications in new energy vehicles are limited.

[0003] For liquid-cooled coolants, they need to have a low dielectric constant, high thermal conductivity, and a wide operating temperature range. The Chinese patent with the authorized publication number CN108841363B in the prior art discloses a coolant for pure electric vehicles, its preparation method and application. The coolant includes the following raw materials in parts by weight: 3-10 parts of N-(2,3-dichloro-6-amino-benzyl) glycine ethyl ester, 1-5 parts of nano metal oxide, 40-50 parts of diol, 4-10 parts of zircon sand, 4-10 parts of sodium dodecylbenzenesulfonate, 3-8 parts of 2-mercapto-4,6-dimethoxypyrimidine, 2-8 parts of boric acid, and 55-65 parts of water. This coolant meets the requirements of the coolant for power batteries in pure electric vehicles, has a significant cooling effect, and can be industrially produced. However, the freezing temperature of this technical solution is in the range of -35°C to -28°C, and its anti-freezing performance needs to be improved.

[0004] The Chinese patent with the publication number CN117844456A discloses an ultra-low conductivity nanofluid coolant, its preparation method and application. The coolant is prepared from the following components in mass percentages: 94-97% of base fluid, 1.0-2.0% of isooctanoic acid, 0.1-1.1% of methylbenzotriazole, 0.05-0.25% of rust inhibitor, 0.009-0.1% of ethylenediaminetetraacetic acid, 0.05-0.1% of sodium molybdate, 0.003-0.015% of defoamer, 0.002-0.004% of colorant, 0.006-0.018% of natural layered nanosheets, and 0.2-0.8% of pH regulator; the base fluid is composed of water and ethylene glycol, and the natural layered nanosheets are selected from at least one of the following: hydrotalcite, kaolin, bentonite, and serpentine. However, the conductivity of this technical solution is greater than 10 us.

[0005] In addition, nano materials are added in the above technical solutions, but their stability is not concerned. Summary of the Invention

[0006] Based on the deficiencies of the existing technology, the purpose of the present invention is to provide a new energy vehicle power battery coolant and its preparation method. The new energy vehicle power battery coolant of the present invention uses specific nano-additives and anti-foaming agents, so that the new energy vehicle power battery coolant has good low dielectric constant, high thermal conductivity and good storage stability.

[0007] To achieve the above object, the technical solution adopted by the present invention is as follows:

[0008] In the first aspect of the present invention, a new energy vehicle power battery coolant is provided. By mass percentage, the raw materials include: 40-60% of diol, 0.2-3% of corrosion inhibitor, 0.1-0.5% of antioxidant, 0.1-0.5% of pH regulator, 0.01-0.05% of anti-foaming agent, 0.005-0.015% of nano-additive, and ionized water to make up the balance to 100%;

[0009] The nano-additive includes ionic flaky nano-minerals, nano-palygorskite and nano-diamond with a mass ratio of 3-5:0.1-0.5:0.1-0.5.

[0010] Preferably, the ionic flaky nano-minerals include montmorillonite nanosheets and / or hydrotalcite nanosheets.

[0011] The montmorillonite nanosheets of the present invention are exfoliated from montmorillonite, and no specific limitation is made on the montmorillonite and the exfoliation method. The montmorillonite that can be cited includes but is not limited to sodium-based montmorillonite, calcium-based montmorillonite, etc.; the exfoliation methods include but are not limited to ultrasonic exfoliation, mechanical exfoliation, etc.

[0012] Preferably, the montmorillonite nanosheets have a sheet diameter of less than 600 nm and a thickness of less than 10 nm.

[0013] More preferably, the montmorillonite nanosheets have a sheet diameter of 300-600 nm and a thickness of less than 6 nm.

[0014] Most preferably, the montmorillonite nanosheets have a sheet diameter of 300 nm and a thickness of less than 4 nm.

[0015] In the embodiment of the present invention, the preparation method of the montmorillonite nanosheets is the preparation method disclosed in the patent with the authorized publication number of CN111592862B. Specifically: mix sodium-based montmorillonite with water, stir it evenly with a magnetic stirrer to obtain a dispersion, place the dispersion in an ultrasonic crusher for exfoliation at an ultrasonic intensity of 450 W, after the ultrasonic treatment, wait for the solution to cool to room temperature, and perform the next exfoliation at the same ultrasonic intensity. Repeat the ultrasonic exfoliation-cooling 3 times, control the ultrasonic time at about 5 minutes each time, and finally centrifuge and dry the mixture to obtain the product.

[0016] Similarly, the preparation method of the hydrotalcite nanosheets of the present invention is not specifically limited, including but not limited to ultrasonic exfoliation and mechanical exfoliation.

[0017] Preferably, the diameter of the hydrotalcite nanosheets is 50-100 nm, and the thickness is 0.5-2 nm.

[0018] More preferably, the diameter of the hydrotalcite nanosheets is 80 nm, and the thickness is 1.2 nm.

[0019] In the embodiments of the present invention, the preparation method of the hydrotalcite nanosheets is the preparation method disclosed in the patent with the authorized publication number: CN112661180B. Specifically:

[0020] (1) Synthesize the NiFe hydrotalcite precursor: Add Ni 2+ and Fe 3+ to the reactor in a certain molar ratio (2:1) and mix evenly. Slowly add an alkaline solution (NaOH, concentration 0.2 mol / L) to keep the pH of the solution in the reactor at about 10. Keep the crystallization at room temperature for 10 h. After the reaction, wash the product by centrifugation with water and dry it to obtain the NiFe-LDH hydrotalcite precursor.

[0021] (2) Prepare ultrathin nanosheets by acoustic levitation method: Disperse the NiFe-LDH hydrotalcite precursor evenly in water to obtain a neutral dispersion of 10 mg / mL. Take a drop of the dispersion and place it in an acoustic levitator. Adjust the set resonance frequency of the acoustic levitator to 10000 Hz to suspend the droplet in the air. After successful suspension, the droplet does not contact the acoustic levitator instrument. After suspending for 10 min, the dispersion is neutral during the suspension process. Collect the droplet to obtain the product.

[0022] More preferably, the ionic flaky nano-minerals include montmorillonite nanosheets and hydrotalcite nanosheets with a mass ratio of 1:1.

[0023] More preferably, the particle size of the nano-palygorskite is less than 1000 nm.

[0024] Even more preferably, the particle size of the nano-palygorskite is 20000 mesh.

[0025] Preferably, the particle size of the nano-diamond is less than 100 nm.

[0026] More preferably, the particle size of the nano-diamond is 50 nm.

[0027] Preferably, the diol includes ethylene glycol and / or propylene glycol.

[0028] Preferably, the corrosion inhibitor is selected from at least one of methylbenzotriazole, benzotriazole, and mercaptobenzothiazole.

[0029] Preferably, the antioxidant includes 2,6 - di - tert - butyl - p - cresol and / or triphenyl phosphite.

[0030] Preferably, the antifoaming agent is a silicone antifoaming agent.

[0031] More preferably, the antifoaming agent is Addital FX580 produced by Huagao New Technology (Nanjing) Co., Ltd.

[0032] Preferably, the pH regulator includes sodium hydroxide and / or potassium hydroxide.

[0033] The second aspect of the present invention provides a preparation method of a power battery coolant for new energy vehicles, comprising the following steps: mixing diol, corrosion inhibitor, antioxidant, pH regulator, antifoaming agent, nano - additive and deionized water in proportion and uniformly to obtain the product.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] 1. In the power battery coolant for new energy vehicles provided by the present invention, nano - additives are added. By the random movement between ionic flaky nano - minerals, a main heat - conducting network is formed. Nano - palygorskite and nano - diamond are filled between ionic flaky nano - minerals to change the lap structure of ionic flaky nano - minerals, forming a high - path heat - conducting network, reducing thermal resistance and enhancing diffusion ability. While improving the thermal conductivity, they also improve the storage stability together (the fibrous structure of nano - palygorskite inhibits particle sedimentation through physical entanglement, and at the same time, its surface hydroxyl groups form hydrogen bonds with the base - liquid molecules to enhance dispersion stability. The rigid surface of nano - diamond reduces the van der Waals force attraction between ionic flaky nano - minerals, thereby preventing agglomeration) and has a low conductivity.

[0036] 2. In the power battery coolant for new energy vehicles provided by the present invention, when nano - additives are added and the ionic flaky nano - minerals include hydrotalcite nanosheets and montmorillonite nanosheets, the hydrotalcite nanosheets and montmorillonite nanosheets can work synergistically to improve the thermal conductivity.

[0037] 3. The present invention unexpectedly finds that the use of a specific type of antifoaming agent improves the stability of the power battery coolant for new energy vehicles. Detailed Embodiments

[0038] In order to have a clearer understanding of the technical features, objectives and effects of the present invention, the specific implementation embodiments are now described in detail.

[0039] The present invention will be further described below in conjunction with embodiments, but the present invention is not limited to the following embodiments. The implementation conditions adopted in the embodiments can be further adjusted according to different requirements of specific use, and the implementation conditions not specified are conventional conditions in the industry. The technical features involved in various embodiments of the present invention can be combined with each other as long as they do not conflict with each other.

[0040] In the following examples and comparative examples, unless otherwise specified, the raw materials used are all commercially available or prepared by conventional methods in the art.

[0041] Basic Example

[0042] Preparation of montmorillonite nanosheets: The preparation method disclosed in the patent with the authorized publication number CN111592862B was adopted. Specifically: Sodium montmorillonite was mixed with water in a ratio of 2 wt%, and a magnetic stirrer was used to fully stir it to make it evenly dispersed to obtain a dispersion. The dispersion was placed in an ultrasonic crusher and peeled at an ultrasonic intensity of 450 W. After the ultrasonic treatment, the solution was cooled to room temperature, and the next peeling was carried out at the same ultrasonic intensity. The ultrasonic peeling-cooling process was repeated 3 times, and the ultrasonic time for each time was controlled at about 5 min. Finally, the mixed solution was centrifuged and dried to obtain montmorillonite nanosheets with a sheet diameter of about 300 nm and an average thickness of less than 4 nm.

[0043] Preparation of hydrotalcite nanosheets: The preparation method disclosed in the patent with the authorized publication number CN112661180B was adopted. Specifically: (1) Synthesis of NiFe hydrotalcite precursor: Ni 2+ and Fe 3+ were added to the reactor in a certain molar ratio (2:1) and mixed evenly. An alkaline solution (NaOH, concentration 0.2 mol / L) was slowly added dropwise to keep the pH of the solution in the reactor at about 10, and crystallization was carried out at room temperature for 10 h. After the reaction, the product was centrifuged and washed with water and then dried to obtain the NiFe-LDH hydrotalcite precursor.

[0044] (2) Preparation of ultrathin nanosheets by acoustic levitation method: The NiFe-LDH hydrotalcite precursor was evenly dispersed in water to obtain a neutral dispersion of 10 mg / mL. A drop of the dispersion was placed in an acoustic levitator, and the set resonance frequency of the acoustic levitator was adjusted to 10000 Hz to make the liquid droplet levitate in the air. After successful levitation, the liquid droplet did not contact the acoustic levitator instrument. After levitation for 10 min, the dispersion was neutral during the levitation process. The liquid droplet was collected to obtain hydrotalcite nanosheets with a sheet diameter of about 80 nm and a thickness of about 1.2 nm.

[0045] Example 1

[0046] A coolant for a power battery of a new energy vehicle, by mass percentage, the raw material composition is: ethylene glycol 50%, benzotriazole 2%, 2,6-di-tert-butyl-p-cresol 0.3%, sodium hydroxide 0.3%, antifoaming agent 0.03%, nano additive 0.01%, and ionic water is added to make up the balance to 100%;

[0047] The nano additive includes hydrotalcite nanosheets, nano palygorskite and nano diamond with a mass ratio of 4:0.2:0.1.

[0048] The nano palygorskite has a mesh number of 20,000 and is purchased from Huachuan Mineral Products Direct Sales Store.

[0049] The nano diamond has a particle size of 50 nm and is purchased from Beijing Decode Gold Technology Co., Ltd.

[0050] The antifoaming agent is an organosilicon antifoaming agent: Addital FX580, purchased from Yihua High-Tech (Nanjing) Co., Ltd.

[0051] The preparation method of the above-mentioned coolant for a power battery of a new energy vehicle is: mixing ethylene glycol, benzotriazole, 2,6-di-tert-butyl-p-cresol, sodium hydroxide, antifoaming agent, nano additive and ionic water in proportion and mixing evenly to obtain.

[0052] Example 2

[0053] A coolant for a power battery of a new energy vehicle, by mass percentage, the raw material composition is: ethylene glycol 50%, benzotriazole 2%, 2,6-di-tert-butyl-p-cresol 0.3%, sodium hydroxide 0.3%, antifoaming agent 0.03%, nano additive 0.01%, and ionic water is added to make up the balance to 100%;

[0054] The nano additive includes montmorillonite nanosheets, nano palygorskite and nano diamond with a mass ratio of 4:0.2:0.1.

[0055] The nano palygorskite has a mesh number of 20,000 and is purchased from Huachuan Mineral Products Direct Sales Store.

[0056] The nano diamond has a particle size of 50 nm and is purchased from Beijing Decode Gold Technology Co., Ltd.

[0057] The antifoaming agent is an organosilicon antifoaming agent: Addital FX580, purchased from Yihua High-Tech (Nanjing) Co., Ltd.

[0058] The preparation method of the above-mentioned coolant for a power battery of a new energy vehicle is: mixing ethylene glycol, benzotriazole, 2,6-di-tert-butyl-p-cresol, sodium hydroxide, antifoaming agent, nano additive and ionic water in proportion and mixing evenly to obtain.

[0059] Example 3

[0060] A new energy vehicle power battery coolant, comprising the following raw materials, calculated by mass percentage: 50% ethylene glycol, 2% benzotriazole, 0.3% 2,6-di-tert-butyl-p-cresol, 0.3% sodium hydroxide, 0.03% anti-foaming agent, 0.01% nano additive, and ionized water to make up the remainder;

[0061] The nano additives include hydrotalcite nanosheets, montmorillonite nanosheets, nano-palygorskite and nano-diamonds in a mass ratio of 2:2:0.2:0.1.

[0062] The mesh number of the nanopalygorskite is 20000 mesh, and it was purchased from Huachuan Mineral Products Direct Sales Store.

[0063] The nanodiamond has a particle size of 50 nm and is purchased from Beijing Dekedaojin Technology Co., Ltd.

[0064] The antifoaming agent is an organosilicon defoaming agent: Addital FX580, which was purchased from Yihua High-tech (Nanjing) Co., Ltd.

[0065] The preparation method of the above-mentioned new energy vehicle power battery coolant is: ethylene glycol, benzotriazole, 2,6-di-tert-butyl-p-cresol, sodium hydroxide, anti-foaming agent, nano additive and ion water are mixed uniformly in proportion.

[0066] Example 4

[0067] A new energy vehicle power battery coolant, comprising the following raw materials, calculated by mass percentage: 50% ethylene glycol, 2% benzotriazole, 0.3% 2,6-di-tert-butyl-p-cresol, 0.3% sodium hydroxide, 0.03% anti-foaming agent, 0.01% nano additive, and ionized water to make up the remainder;

[0068] The nano additives include hydrotalcite nanosheets, montmorillonite nanosheets, nano-palygorskite and nano-diamonds in a mass ratio of 1.5:1.5:0.1:0.3.

[0069] The mesh number of the nanopalygorskite is 20,000 mesh, and it was purchased from Huachuan Mineral Products Direct Sales Store.

[0070] The nanodiamond has a particle size of 50 nm and is purchased from Beijing Dekedaojin Technology Co., Ltd.

[0071] The antifoaming agent is an organosilicon defoaming agent: Addital FX580, which was purchased from Yihua High-tech (Nanjing) Co., Ltd.

[0072] The preparation method of the above-mentioned new energy vehicle power battery coolant is: ethylene glycol, benzotriazole, 2,6-di-tert-butyl-p-cresol, sodium hydroxide, anti-foaming agent, nano additive and ion water are mixed uniformly in proportion.

[0073] Example 5

[0074] A power battery coolant for new energy vehicles, by mass percentage, the raw material composition is: ethylene glycol 50%, benzotriazole 2%, 2,6 - di - tert - butyl - p - cresol 0.3%, sodium hydroxide 0.3%, antifoaming agent 0.03%, nano - additive 0.01%, and ionized water to make up the balance to 100%;

[0075] The nano - additive includes hydrotalcite nanosheets, montmorillonite nanosheets, nano - palygorskite, and nano - diamond with a mass ratio of 2.5:2.5:0.5:0.2.

[0076] The mesh number of the nano - palygorskite is 20,000 meshes, purchased from Huachuan Mineral Products Direct Sales Store.

[0077] The particle size of the nano - diamond is 50 nm, purchased from Beijing Decode Island Gold Technology Co., Ltd.

[0078] The antifoaming agent is an organosilicon defoamer: Addital FX580, purchased from Yihua High - Tech (Nanjing) Co., Ltd.

[0079] The preparation method of the above - mentioned power battery coolant for new energy vehicles is: mixing ethylene glycol, benzotriazole, 2,6 - di - tert - butyl - p - cresol, sodium hydroxide, antifoaming agent, nano - additive, and ionized water in proportion and mixing them evenly.

[0080] Comparative Example 1

[0081] The difference from Example 3 is that the nano - additive includes hydrotalcite nanosheets, montmorillonite nanosheets, and nano - diamond with a mass ratio of 2:2:0.3; the rest are the same.

[0082] The preparation method of the above - mentioned power battery coolant for new energy vehicles is the same as that of Example 3.

[0083] Comparative Example 2

[0084] The difference from Example 3 is that the nano - additive includes hydrotalcite nanosheets, montmorillonite nanosheets, and nano - palygorskite with a mass ratio of 2:2:0.3; the rest are the same.

[0085] The preparation method of the above - mentioned power battery coolant for new energy vehicles is the same as that of Example 3.

[0086] Comparative Example 3

[0087] The difference from Example 3 is that the nano-additive includes nano-talc powder, nano-bentonite, nano-palygorskite and nano-diamond with a mass ratio of 2:2:0.2:0.1; the particle size of the nano-talc powder is 30 nm and it is purchased from Shanghai Wanzhao Fine Chemical Co., Ltd.; the particle size of the nano-bentonite is 50 nm and it is purchased from Guangzhou Gaoxin Trading Co., Ltd.; the rest are the same.

[0088] The preparation method of the above new energy vehicle power battery coolant is the same as that of Example 3.

[0089] Comparative Example 4

[0090] The difference from Example 3 is that the nano-additive includes hydrotalcite nanosheets, montmorillonite nanosheets, nano-palygorskite and nano-diamond with a mass ratio of 3:3:0.6:0.1; the rest are the same.

[0091] The preparation method of the above new energy vehicle power battery coolant is the same as that of Example 3.

[0092] Comparative Example 5

[0093] The difference from Example 3 is that the nano-additive includes hydrotalcite nanosheets, montmorillonite nanosheets, halloysite nanotubes and nano-diamond with a mass ratio of 2:2:0.2:0.1; the halloysite nanotubes are purchased from Guangdong Jinna New Materials Technology Co., Ltd.; the rest are the same.

[0094] The preparation method of the above new energy vehicle power battery coolant is the same as that of Example 3.

[0095] Comparative Example 6

[0096] The difference from Example 3 is that the defoamer is silicone defoamer: DOWSIL TW 62, purchased from Shanghai Kaishida Chemical New Materials Co., Ltd.; the rest are the same.

[0097] The preparation method of the above new energy vehicle power battery coolant is the same as that of Example 3.

[0098] The new energy vehicle power battery coolants obtained in Examples 1-5 were tested for freezing point (test method: SH / T0090), boiling point (test method: SH / T0089), conductivity (test method: GB29743.2), storage stability (test method: GB29743.2), and thermal conductivity (test method: tested using a thermal conductivity tester): The test results are shown in Table 1:

[0100] Table 1

[0101]

[0102] As can be seen from Table 1, the battery coolants for new energy vehicles in Examples 1-5 have good storage stability, low conductivity, high thermal conductivity, and a wide operating temperature range; as can be seen from Examples 1 to 3, in Example 3, due to the simultaneous use of hydrotalcite nanosheets and montmorillonite nanosheets, a synergistic effect is exhibited compared with Examples 1 and 2, and the thermal conductivity is significantly improved.

[0103] The battery coolants for new energy vehicles obtained in Comparative Examples 1-6 were tested for conductivity (test method: GB29743.2), storage stability (test method: GB 29743.2), and thermal conductivity (test method: tested using a thermal conductivity tester): The test results are shown in Table 2:

[0104] Table 2

[0105]

[0106] As can be seen from Table 2, in Comparative Example 1, nano-attapulgite was replaced with an equal mass of nano-diamond, that is, the amount of nano-diamond was increased. Not only was the thermal conductivity not improved, but precipitation occurred and the conductivity increased. In Comparative Example 2, nano-diamond was replaced with an equal mass of nano-attapulgite, and the thermal conductivity decreased significantly. In Comparative Example 3, hydrotalcite nanosheets and montmorillonite nanosheets were replaced with ordinary nano-talc powder and nano-bentonite, and precipitation occurred and the thermal conductivity decreased significantly. In Comparative Example 4, the mass ratio of hydrotalcite nanosheets, montmorillonite nanosheets, nano-attapulgite, and nano-diamond was not within the preferred range, and precipitation occurred, the conductivity increased, and the thermal conductivity decreased significantly. In Comparative Example 5, nano-attapulgite was replaced with an equal mass of halloysite nanotubes, and precipitation occurred and the thermal conductivity decreased significantly. In Comparative Example 6, the type of organic defoamer was replaced, and sedimentation occurred.

[0107] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than a limitation on the protection scope of the present invention. Any simple modification or equivalent replacement made by those of ordinary skill in the art to the technical solution of the present invention does not depart from the essence and scope of the technical solution of the present invention.

Claims

1. A coolant for power batteries of new energy vehicles, characterized in that, By mass percentage, the raw materials include: 40 - 60% of diol, 0.2 - 3% of corrosion inhibitor, 0.1 - 0.5% of antioxidant, 0.1 - 0.5% of pH regulator, 0.01 - 0.05% of antifoaming agent, 0.005 - 0.015% of nano additive, and ionized water to make up the balance to 100%; The nano additive includes ionic flaky nano minerals, nano palygorskite, and nano diamond with a mass ratio of 3 - 5:0.1 - 0.5:0.1 - 0.

5.

2. The coolant for the power battery of a new energy vehicle according to claim 1, wherein The ionic flaky nano minerals include montmorillonite nano sheets and / or hydrotalcite nano sheets.

3. The coolant for the power battery of a new energy vehicle according to claim 2, wherein The montmorillonite nano sheets have a sheet diameter of less than 600 nm and a thickness of less than 10 nm.

4. The coolant for the power battery of a new energy vehicle according to claim 2, wherein The hydrotalcite nano sheets have a sheet diameter of 50 - 100 nm and a thickness of 0.5 - 2 nm.

5. The coolant for the power battery of a new energy vehicle according to claim 1, characterized in that, The ionic flaky nano minerals include montmorillonite nano sheets and hydrotalcite nano sheets with a mass ratio of 1:

1.

6. The power battery coolant for new energy vehicles according to any one of claims 1-5, characterized in that, The nano palygorskite has a particle size of less than 1000 nm.

7. The coolant for the power battery of a new energy vehicle according to any one of claims 1-5, characterized in that, The nano diamond has a particle size of less than 100 nm.

8. The coolant for the power battery of a new energy vehicle according to any one of claims 1-5, characterized in that The diol includes ethylene glycol and / or propylene glycol.

9. The coolant for the power battery of a new energy vehicle according to any one of claims 1-5, characterized in that The antifoaming agent is an organosilicon defoamer; the defoamer is Addital FX580.

10. The preparation method of the power battery coolant for new energy vehicles according to any one of claims 1-9, characterized in that, It includes the following steps: Mix the diol, corrosion inhibitor, antioxidant, pH regulator, antifoaming agent, nano additive, and ionized water evenly in proportion to obtain the product.

Citation Information

Patent Citations

  • A coolant for pure electric vehicles, its preparation method and application

    CN108841363B

  • Montmorillonite nanosheets / water nanofluids and their preparation methods

    CN111592862B

  • Ultrathin hydrotalcite nanomaterials and their preparation methods

    CN112661180B

  • Low-conductivity cooling liquid and preparation method thereof

    CN115418202A

  • Fuel cell cooling liquid with self-maintenance and leaking stoppage functions and preparation method of fuel cell cooling liquid

    CN116574490A

Cited By

  • Low-conductivity cooling liquid suitable for new energy automobile and preparation method of low-conductivity cooling liquid

    CN121319889A